Poor treatment tolerance in head and neck cancer patients with low muscle mass. Issue 4 (12th January 2022) - Mascarella, Marco A.; Patel, Terral; Vendra, Varun; Gardiner, Lauren; Kergoat, Marie‐Jeanne; Kubik, Mark W.; Solari, Mario G.; Snyderman, Carl H.; Traylor, Katie S.; Ferris, Robert L.; Kim, Seungwon; Duvvuri, Umamaheswar; et al.
Abstract: Background: We ascertain the role of a low cervical paraspinal skeletal muscle index (CPSMI) as a biomarker for poor treatment tolerance in patients with operable mucosal head and neck squamous cell carcinoma (HNSCC). Methods: A prospective cohort of patients with operable HNSCC requiring microvascular reconstruction was evaluated. Low CPSMI was calculated using preoperative CT neck imaging. Poor treatment tolerance, a composite measure of incomplete therapy or severe morbidity/mortality during treatment, was the primary outcome. Results: One hundred and twenty‐seven patients underwent extirpative surgery with a mean age was 60.5. Poor treatment tolerance occurred in 71 (56%) patients with 21 not completing recommended adjuvant therapy and 66 having severe treatment‐related morbidity. A low CPSMI was independently associated with poor treatment tolerance (OR 2.49, 95%CI 1.10–5.93) and delay to adjuvant therapy (OR 4.48, 95%CI 1.07–27.6) after adjusting for multiple confounders. Conclusion: Low CPSMI was independently associated with poor treatment tolerance in patients with operable HNSCC.